Pathogenetic effects of feed intake containing of fumonisin (Fusarium verticillioides) in early broiler chicks and consequences on weight gain. (October 2020) - Sousa, Marcela C.S.; Galli, Gabriela M.; Alba, Davi F.; Griss, Luiz Gustavo; Gebert, Roger R.; Souza, Carine F.; Baldissera, Matheus D.; Gloria, Eduardo M.; Mendes, Ricardo E.; Zanelato, Gabrielli O.; Gris, Anderson; Boiago, Marcel M.; et al.
Abstract: Fusarium verticillioides is often responsible for contamination of poultry feed with the mycotoxin fumonisin. The objective of the study was to determine whether fumonisin-contaminated feed in the early phase of broiler chicks causes oxidative imbalances and interferes with weight gain. One-day-old male Cobb 500 broiler chicks (n = 80) were divided into four treatments of 20 birds each, all of which were fed basal feed until the 11th day of age. From day 12, some birds were challenged with fumonisin in the feed: Control (T0) continued receiving the basal ration; treatments T1, T2, and T3 were given feed experimentally contaminated with fumonisin at concentrations of 2.5 ppm, 5 ppm and 10 ppm, respectively. After the 5th (day 17) and 10th (day 21) days, ten birds from each treatment were euthanized for blood and tissue collection to measure histopathological, biochemical and oxidative stress markers. All animals were weighed individually at the beginning of the experiment (day 12), and at 17 and 21 days of age. Birds that ingested 10 ppm of fumonisin (T3) had lower (P < 0.05) weight gain compared to those in T0. At 21 days, the body weights of the T1, T2 and T3 chicks were 1.3%, 8.97% and 18.7% lower, respectively, than those of T0. No histological lesions in the livers were observed for any treatment; however, higher levels of reactive oxygen species (ROS: day 21) and lipoperoxidation (LPO: days 17 and 21) were observed, associated with lower liver activity of the enzymes superoxide dismutase (SOD: day 21), glutathione peroxidase (GPx: day 17 and 21) and glutathione S-transferase (GST: day 21) when birds consumed 5 or 10 ppm of fumonisin. In serum, LPO levels and SOD and GPx activities were lower for groups consuming high doses of fumonisin in the diet (T2 and T3); ROS levels and GST activity were higher in these birds. Birds that consumed fumonisin-containing diets had lower levels of alanine aminotransferase, total protein and albumin (T3); as well as lower serum glucose levels (days 17 and 21), uric acid and triglycerides (day 21) in T3 than in T0. At 21 days, there were smaller crypt sizes and intestinal villi in birds that consumed high levels of fumonisin. These results suggest that fumonisin (10 ppm) in chick diet causes hepatic oxidative stress and impairs intestinal health, consequently negatively affecting weight gain. Highlights: Mycotoxins are known to reduce animal performance, growth and feed efficiency. Low-dose fumonisin in early broiler chick diets causes hepatic oxidative stress. Birds that ingested fumonisin at dose 10 ppm for 10 days had 18% lower body weight.